Sustainable development goals and carbon reduction: Insights from universities in Eastern Indonesia - Anggraini, Nani Anggraini; Akrim, Djusdil; Muis, Ramdiana; Hutagalung, Ira; Tawakkal, Irfan; Al Fariz, Reza Darma; Rachman, Indriyani; Matsumoto, Toru (Talenta Publisher, 2025)
This study employed a mixed methods design to analyse university students' knowledge of the Sustainable Development Goals (SDGs), their practices toward carbon reduction, and their innovative ideas for carbon mitigation. The main aim of this research is to examine how students’ understanding of the SDGs relates to their actual carbon reduction practices and to identify innovative solutions they propose for environmental sustainability. The research surveyed 123 students from 11 academic programs across seven universities in Eastern Indonesia. Quantitative results showed no significant differences in carbon reduction practices among students from various academic programs (F = 0.720; p = 0.674). A significant but very weak correlation was found between SDG knowledge and positive practices toward carbon reduction (r = 0.152; p = 0.047). The qualitative analysis identified eight themes of innovation, with a majority focusing on reforestation (33%) and the 3R waste management system (31%). Notably, technology-based ideas constituted only 8% of the responses. The study's main limitations include a sample imbalance, with 39.5% of participants from Environmental Engineering, and the use of convenience sampling, which necessitates caution when generalizing the findings. The results suggest the need for a holistic approach that integrates education, practical implementation, supportive facilities, and technological innovation. Recommendations include: (1) integrating SDGs into the curriculum, (2) developing a gamified, collaborative digital platform, and (3) fostering interdisciplinary collaboration to create contextual solutions